A new light on the meiotic DSB catalytic complex. (June 2016) - Robert, Thomas; Vrielynck, Nathalie; Mézard, Christine; de Massy, Bernard; Grelon, Mathilde
Abstract: Meiotic recombination is initiated by the formation of programmed DNA double-strand breaks (DSBs). More than 15 years ago, Spo11 was identified as the protein responsible for meiotic DSB formation, notably because of its striking similarities with the A subunit of topoisomerase VI (TopoVI). TopoVI are enzymes that modify DNA topology by generating transient DSBs and are active as heterotetramers, composed of two A and two B subunits. A2 dimers catalyse the DNA cleavage reaction, whereas the B subunits regulate A2 conformation, DNA capture, cleavage and re-ligation. The recent identification in plants and mammals of a B-like TopoVI subunit that interacts with SPO11 and is required for meiotic DSB formation makes us to reconsider our understanding of the meiotic DSB catalytic complex. We provide here an overview of the knowledge on TopoVI structure and mode of action and we compare them with their meiotic counterparts. This allows us to discuss the nature, structure and functions of the meiotic TopoVI-like complex during meiotic DSB formation.